Metagenomic-Metabolomic Mining of Kinema, a Naturally Fermented Soybean Food of the Eastern Himalayas - Kharnaior, Pynhunlang; Tamang, Jyoti Prakash (Frontiers in Microbiology, 2022)
Kinema is a popular sticky fermented soybean food of the Eastern Himalayan regions of India, Nepal and Bhutan. We hypothesized that some dominant bacteria in kinema may contribute in formation of targeted and non-targeted metabolites for health benefits, hence, we studied the microbiome-metabolites mining of kinema. A total of 1,394,094,912 bp with an average of 464,698,304 ± 120,720,392 bp was generated from kinema metagenome, which resulted in identification of 47 phyla, 331 families, 709 genera and 1560 species. Bacteria (97.78%) were the most abundant domain with the remaining domains of viruses, eukaryote and archaea. Firmicutes (93.36%) was the most abundant phylum with 280 species of Bacillus among which B. subtilis was the most dominant species in kinema followed by B. glycinifermentans, B. cereus, Brevibacillus borstelensis, B. licheniformis, B. thermoamylovorans, Kurthia sp. 11kri321, B. coagulans, B. circulans, B. paralicheniformis. Predictive metabolic pathways revealed the abundance of genes associated with metabolism (60.66%) resulting into 216 sub-pathways. A total of 361 metabolites were identified by metabolomic analysis (LC-MS). Presence of metabolites such as chrysin, swainsonine and 3-hydroxy-L-kynurenine (anticancer activity), benzimidazole (antimicrobial, anticancer and anti-HIV activities) and compounds with immunomodulatory effects in kinema support its therapeutic potential. The correlation between the abundant species of Bacillus with primary and secondary metabolites were constructed with a bivariate result. This study proves that Bacillus spp. contribute the formation of many targeted and untargeted metabolites in kinema for health promoting benefits.